Response of essential-oil yield of aromatic and medicinal plants to different harvesting strategies - Zuazo, Victor Hugo Durán; García-Tejero, Iván Francisco; Gálvez Ruiz, Baltasar; Cermeño Sacristán, Pedro; Cuadros Tavira, Simón (Comunicata Scientiae, 2019)
The demand for aromatic and medicinal plants (AMPs) is growing worldwide, and most of them are from the wild collection. Today there is a consensus that for industrial purposes the AMPs must be cultivated. Many studies have shown the importance of the collection strategy used to guarantee the plant regeneration, and soil protection against erosion process in mountainous areas in the Mediterranean region. In this work, during three-year monitoring period we compared in four AMPs two harvest strategies by cutting biomass in 25% (BHI25) and 50% (BHI50) of oregano (Origanum bastetanum L.), lavender (Lavandula lanata L.); sage (Salvia lavandulifolia V.); and santolina (Santolina rosmarinifolia L.) in order to assess their effect on essential-oil content, and to be consistent with both plant and soil conservation in Mediterranean steeply sloping areas. The experimental plots were located in Lanjarón (Granada, SE Spain), on a 20% slope. According to the findings the strategy BHI50 of fresh herb of oregano, lavender, sage, and santolina produced essential-oil yield of 13.2 ± 1.74, 17.3 ± 1.69, 9.7 ± 5.21, and 10.8 ± 2.00 L·ha-1, respectively. Since significant differences were found between BHI25 and BHI50 strategies for harvest and distillation of aromatic plants, we recommend a rational harvest, leaving the 50% of the plant biomass in the field to avoid the soil degradation. In addition, with this rational harvest strategy encourages the sustainable AMP cultivation without significant alterations for essential-oil yields, and at the same time guaranteeing the regrowth, and conservation of them in its habitat. Therefore, encouragement local decision-making measures regarding environmental compatibility, social acceptability and economic viability in land use and management will be crucial. Otherwise, the inappropriate harvest of aromatic shrubs in mountain areas compromises land conservation.